Investigating the Fouling Models of the Microfiltration Mixed Matrix Membranes-Based Oxide Nanoparticles Applied for Oil-in-Water Emulsion Separation - Sadek, Sara A.; Al-Jubouri, Sama M.; Al-Batty, Sirhan (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Membrane fouling is a major problem encountered in the use of microfiltration (MF) processes to separate the emulsified oil from water. This work involves assessing the efficacy of removing oil-in-water emulsion (O/W emulsion), and evaluating fouling resistance by studying the membrane morphology before and after fouling, and after washing with different cleaning solutions via field emission scanning electron microscopy (FESEM) analysis. Also, the fundamental mechanism involved in the flux drop during crossflow MF has been assessed using models such as the Hermia blocking models and the modified model by Field. The standard and intermediate pore blocking models provided the best prediction for experimental behavior when analyzing the decay in the flux with time for the bio silicon oxide/polyvinylchloride (B-SiO2/PVC) membrane and the stannic oxide/polyvinylchloride (SnO2/PVC) membrane. This research established regression equations of the flux for both membranes in which these equations are highly correlated with R2 of 98.33% for B-SiO2/PVC and R2 of 99.52% for SnO2/PVC using the surface response methodology (RSM). The high flux recovery ratio (FRR) is indicative of the improved antifouling feature of the manufactured membranes where it was 96.8% for B-SiO2/PVC and 94.6% for SnO2/PVC. The results obtained by Hermia and Field were in good agreement with RSM analysis supporting the standard pore-blocking mechanism.